Implementasi Permenpan RB Nomor 4 Tahun 2014 Tentang Jabatan Fungsional Polisi Pamong Praja Dan Angka Kreditnya Pada Satpol PP Dan Kebakaran Kabupaten Trenggalek - Bambang Wiyono; Imam Fachruddin; Daimul Abror; Teguh Pramono; Muhamad Chairul Basrun Umanailo (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
This research was motivated by observational data that showed the promotion and level of the Functional Position of the Pamong Praja Police (JF Pol PP) in the Pamong Praja and Fire Police Unit of Trenggalek Regency was not following the RB Regulation number 4 of 2014. The purpose of this study was to determine the inhibiting factors that resulted in the process of promotion and promotion to the rank of the Pamong Praja Police Functional Position. The type of research used in this study is a descriptive qualitative approach using the theoretical method of George Edward III, which is based on 4 (four) aspects, namely communication, resources, disposition, and bureaucratic structure. The source of this research data is the Functional Officer of the Civil Service Police in the Civil Service and Fire Police Unit of Trenggalek Regency. The results showed that the process of promotion and promotion was still not following the periodization due to the lack of understanding of the profile of the position concerned. Among them, most of the functional officers of the civil service police still have not conducted an inventory of the activities carried out, resulting in difficulties in obtaining a Credit Number Determination (PAK) which is the main requirement in the promotion process and promotion. From the data, it is recommended that functional officials of the civil service police understand the profile of the position better to support the future career path.